The Effect of Self-Efficacy on Career Decision Making in Final Year Students - Milensia Risma Rodinda; Nur Eva (Indonesian Psychological Research, 2023)
The objectives of the study are to understand career decision-making in final-year psychology students at the state university of Malang, to understand self-efficacy in final-year students at state universities in Malang, and to determine if self-efficacy and career satisfaction are influenced in final-year psychology students at the state university of Malang. This study employs a quantitative, descriptive methodology using scale-shaped instruments for data collection, which are communicated via Google Forms. The General Self-Efficacy Scale (GSES), created by Schwarzer and Jerusalem, is used to gauge self-efficacy (1995). Heru (2015) developed a test to assess career decision-making based on the Miller and Tiedeman hypothesis (Sharf, 1992). (2015). One hundred twenty people made up the study's samples. Purposive sampling is a sampling technique. Simple regression analysis is used in data analysis approaches. R2 = 37.7% of the data in this study's results were gathered, with a p-value of 0.000. It is impossible to claim that self-efficacy influences career decision-making in a way that accounts for 37.7% of it, while other factors that have not been the subject of research impact the other 62.3 percent.